Sensitive Periods of Moving on Mental Health and Academic Performance Among University Students - Li, Ming; Li, Wen-Qiao; Li, Liman Man Wai (Frontiers in Psychology, 2019)
Moving within and across nations becomes a non-reversible increasing trend globally. The current research investigated the unique effect of residential mobility at different developmental stages (i.e., early childhood, late childhood, and adolescence) on university students’ mental health and academic performance. In addition, we investigated the role of two different types of coping resources, i.e., resilience and family income, in moderating the negative effect of residential mobility. The data from 3753 first-year university students revealed that: 1) residential mobility in late childhood and adolescence (but not in early childhood) predicted poorer mental health among university students; 2) high resilience and higher family income alleviated the association of residential mobility in adolescence and mental health status; and 3) residential mobility in adolescence (but not in early childhood and late childhood) was associated with poorer academic performance but this pattern was not moderated by resilience or family income. The theoretical implications and practical implications of these findings were discussed.